Enzymatic inactivation of coffee leaves for use in beverages (Research, Society and Development, 2020)
In the processing of vegetable leaves, for the preparation of beverages, enzymatic inactivation is necessary to eliminate the characteristic taste of green leaves. The objective of this work was to study the roasting of coffee leaves, in order to inactivate the enzymes, aiming to obtain a drink in the tea category. The enzymatic inactivation was carried out, in a rotating roaster, at different temperatures (60-100°C), and at different times (30-180s). The drying equilibrium curve was performed on 30 sheets, at different temperatures (40-105°C), in a forced air circulation oven. The effective diffusivity, according to Fick's Law, was calculated for temperatures 60-100°C. To inactivate the enzymes and obtain a drink, it is recommended that the leaves are roasted, at temperatures above 80°C, with a minimum time of 80s.